A ship navigator's mental workload using salivary NO3− concentration for simulator-based experiment. Issue 1 (2nd January 2017) - Kitamura, Kenichi; Murai, Koji; Wakida, Shin-ichi; Mitomo, Nobuo; Fukushi, Keiichi
Abstract: We challenge an evaluation of a ship bridge teammate's mental workload. If we are able to evaluate using a quantitative index for a veteran navigator, it means we get more essential skill for practical education, for example, the educators show students the detail suggestion of skill of ship maneuvering for simulator-based and real ship handling. We think that the both of performance and mental workload are important to evaluate the skill of ship maneuvering; however, the mental workload doesn't use yet. Regarding the index of mental workload, the heart rate variability (HRV) is popular for a lot of research fields. We usual use HRV, nasal temperature, and try saliva. The saliva is possible to evaluate the mental workload on the spot for ship maneuvering. We hope simple measurement and clear result for the index, and it is practical method in a classroom. The spot measurement is one of research target. In this study, we aim salivary NO3 − concentration for simulator-based experiment. We show the results of the response of salivary NO3 − for narrow passage and entering a port in which the navigator needs the judgement for safe navigation.